Three essays on asset pricing. - Wang, Ying. (2013)
Kinder, Lyndenberg, and Domini (KLD) provide Corporate Social Responsibility (CSR) scores for corporations. Using these scores, we classify institutions into socially responsible institutions (SRI) and non-socially-responsible institutions (NSRI) based on the value weighted Corporate Social Responsibility (CSR) scores of their portfolio holdings. We find that after controlling for CSR scores, the stocks held by NSRI‘s realized higher returns in the next quarter. These results are especially strong for high CSR stocks. Our interpretation is that excessive CSR policy is value-destroying and that higher NSRI ownership stifles future CSR activity. Consistent with the hypothesis, we find that an increase in NSRI ownership predicts subsequent cutbacks in CSR policies, especially for high CSR and poorly performing firms. Furthermore, we observe return reversals indicating that firms reverse some of the earlier gains in stock prices from the increase of NSRI ownership if they fail to cutback CSR as expected.